2018
DOI: 10.1002/pros.23743
|View full text |Cite
|
Sign up to set email alerts
|

Sox7 negatively regulates prostate‐specific membrane antigen (PSMA) expression through PSMA‐enhancer

Abstract: Background PSMA expression in the prostate epithelium is controlled by a cis‐element, PSMA enhancer (PSME). PSME contains multiple binding sites for Sox proteins, and in this study, we identified Sox7 protein as a negative regulator of PSMA expression through its interaction with PSME. Methods The statistical correlation between Sox7 and PSMA mRNA expression was evaluated using five prostate cancer studies from cBioportal. In vitro and in vivo interaction between Sox7 and PSME was evaluated by chromatin immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It has not been addressed whether isoform 2 of SOX7 is imported into the nucleus or whether it has a cytoplasmic function. However, in a prostate cancer cell line, which mainly expresses isoform 2, transcriptional activation of enhancers targeted by SOX7 was not dependent on isoform 2 and could only be rescued by ectopic expression of isoform 1, suggesting that the G-patch-containing SOX7 might have additional roles in cells where it is expressed (Peng et al 2019).…”
Section: In Transcription Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…It has not been addressed whether isoform 2 of SOX7 is imported into the nucleus or whether it has a cytoplasmic function. However, in a prostate cancer cell line, which mainly expresses isoform 2, transcriptional activation of enhancers targeted by SOX7 was not dependent on isoform 2 and could only be rescued by ectopic expression of isoform 1, suggesting that the G-patch-containing SOX7 might have additional roles in cells where it is expressed (Peng et al 2019).…”
Section: In Transcription Regulationmentioning
confidence: 97%
“…It inhibits Wnt signalling by directly binding β-catenin via its central domain and blocking β-cateninmediated transcription activation (Takash et al 2001;Zorn et al 1999). Interestingly, only SOX7 isoform 2 encodes a canonical G-patch motif, which replaces the N-terminal nuclear localization signal of isoform 1 (Peng et al 2019). It has not been addressed whether isoform 2 of SOX7 is imported into the nucleus or whether it has a cytoplasmic function.…”
Section: In Transcription Regulationmentioning
confidence: 99%
“…A previous study demonstrated that the expression of SOX7 mRNA was frequently downregulated in many human cancer cell lines and tumor tissues [ 12 ]. Some members of the SOX family are negative regulators of the WNT-b-catenin-TCF signaling pathway [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…SOX7, a member of subgroup F along with SOX17 and SOX18, has been reported to regulate hematopoiesis and cardiogenesis originally. Furthermore, accompanied with the increasing evidence, SOX7 in particular has also been revealed to be a tumor suppressor in a number of human cancers [ 12 ]. For example, its downregulation was observed in tumors from the ovary, stomach, and lungs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was merely reported that PSMA expression was regulated by a cis-element, the PSMA enhancer (PSME), in prostate epithelium [32]. Moreover, PSME could be negatively regulated by Sox7 protein [33]. As the above mechanism was not exclusive to tumors, it could not apply to our study, which unraveled the speci c mechanism of GBMinduced PSMA upregulation.…”
Section: Discussionmentioning
confidence: 73%